Embodied cognition: looking inward - Nowakowski, Przemysław R. (Hybris, 2017)
The body is a highly complex, coordinated system engaged in coping with many environmental problems. It can be considered as some sort of opportunity or obstacle, with which internal processing must deal. Internal processing must take into account the possibilities and limitations of the particular body. In other words, even if the body is not involved in the realization of some cognitive explicit task, it is not a neutral factor of our understanding of why a system solves a task in one way or another. Therefore, when conducting research on embodiment and the body’s cognitive system we should not neglect internal, cognitive processing. I appeal to Goldman’s research on embodied cognition to sketch the broader framework for internal processing in embodied cognition. I believe that even if we don’t accept Goldman’s approach as the viable proposal for embodied cognition in general, it’s a quite natural starting point for our analysis. Goldman (2012; 2014, and with de Vignemont 2009) argue for the essential role of the bodily formats or bodily codes (respectively: B-formats and B-codes) in embodied cognition. B-codes are here described as the processing of regions or sub-regions of the central nervous system. They are primarily employed for body control or monitoring, and reused for cognitive tasks. Beyond doubt, this conception provides an excellent starting point for analyzing the internal (mostly neural) processing in cases of embodied cognition. At the end of this paper, I will argue that the embodiment of cognition needs a conceptual twist. Following Keijzer’s (2015) interest in the evolution of the nervous system, and the minimal forms of cognition, I argue that in investigating embodied cognition, we should investigate the role played by cognitive processing for specific kinds of organisms, meaning organisms with a body of a particular morphology (size, shape, kinds, and distribution of sensors and effectors). Doing that, I refer to some conceptual and empirical considerations. I will also try to show that research on embodied cognition is still not sufficiently anchored in evolutionary and comparative studies on cognition, nor on the nervous system and body morphology. Bigger reliance on these kinds of studies, will make it make possible to gain a deeper understanding of internal processing in embodied cognition.